Development of an E-Jobsheet for Clutch System Overhaul Based on Flip PDF Corporate Software for Grade XI Students of SMK Negeri 3 Semarang - Muhammad Khilmi Mubarok; Angga Septiyanto; Lelu Dina Apristia; Mohammad Burhan Rubai Wijaya (Universitas Negeri Semarang, 2025)
This study aims to develop an e-jobsheet for manual clutch system overhaul based on Flip PDF Corporate software for Grade XI students at SMK Negeri 3 Semarang. The e-jobsheet is a digital worksheet designed to replace conventional jobsheets and was created in HTML5 format using Flip PDF Corporate software. It can be accessed via electronic devices such as smartphones or computers connected to the internet. This research follows a Research and Development approach using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This study used a pre-experimental design with a one-group pretest-posttest model involving one class of students. The feasibility of the product was evaluated by media and material experts, resulting in scores of 96.87% and 89.95%, respectively, categorized as “very feasible.” The average pretest score was 60.4, while the posttest average was 86.5, with a gain of 43.21%. A paired-samples t-test showed p < 0.001, and the N-Gain score reached 0.6532, indicating a significant and effective improvement. Additionally, student response questionnaires yielded a satisfaction score of 93%, also classified as very positive student response. These findings confirm that the developed e-jobsheet is feasible and moderately effective in supporting learning outcomes.